68.8k views
0 votes
5(- 3x - 2) - (x - 3) = -4(4x + 5) + 13 pls help

2 Answers

1 vote

answers

All real numbers are solutions

step by step

5(−3x−2)−(x−3)=−4(4x+5)+13

Step 1: Simplify both sides of the equation.

5(−3x−2)−(x−3)=−4(4x+5)+13

5(−3x−2)+−1(x−3)=−4(4x+5)+13(Distribute the Negative Sign)

5(−3x−2)+−1x+(−1)(−3)=−4(4x+5)+13

5(−3x−2)+−x+3=−4(4x+5)+13

(5)(−3x)+(5)(−2)+−x+3=(−4)(4x)+(−4)(5)+13(Distribute)

−15x+−10+−x+3=−16x+−20+13

(−15x+−x)+(−10+3)=(−16x)+(−20+13)(Combine Like Terms)

−16x+−7=−16x+−7

−16x−7=−16x−7

Step 2: Add 16x to both sides.

−16x−7+16x=−16x−7+16x

−7=−7

Step 3: Add 7 to both sides.

−7+7=−7+7

0=0

User BigSN
by
4.6k points
2 votes

Answer:

infinite solutions

Explanation:

5(- 3x - 2) - (x - 3) = -4(4x + 5) + 13

Ditribute

-15x -10 -x +3 = -16x - 20+13

Combine like term

-16x -7 = -16x -7

Add 16x to each side

-16x+16x -7 = -16x+16x-7

-7 =-7

This is always true so we have infinite solutions.

User Raythurnevoid
by
4.9k points